Ocorrência de ectoparasitas em tilápia do Nilo (Oreochromis niloticus), nas linhagens Chitralada e Gift, em diferentes densidades e alimentadas com dois níveis de proteína - Braccini, Graciela Lucca (2007)
It was observed ectoparasites occurrence and allometric condition factor in Nile Tilapia (Oreochromis niloticus), in Chitralada and GIFT strains cultivated in cages with different densities and ponds, using rations with two protein levels. Tegument scraping and gills samples from reverted male were evaluated, in two experiment phases. The first was carried out with 240 fingerlings from 18 glass fiber boxes with 500L using three stocking density. Total occurrence in Chitralada strain (30, 40 and 50 fish/m3 of stocking density) was 72.2%, 83.3% and 59.5%, with Trichodina predominance (38.9%, 63.3% and 26.2%), respectively. For GIFT strain, at same stocking density, it was identified 83.3%, 73.3% and 80.9%, also with higher Trichodina predominance (33.3%, 73.3% and 45.2%), respectively. In the second phase, 90 fish from each strain, from two ponds (140 m2 each one) and fed with two crude protein levels (25 and 30%) were evaluated. Total occurrence for Chitralada and GIFT strains with 25% CP was 86.7% and 76.7%, respectively, and for 30% CP was 60%. The 30% CP level, independent of strain, had the lowest parasite occurrence. The best result for the allometric condition factor index was observed for GIFT strain, at 25% of crude protein in ration, being inversely proportional to the weight gained by fishes.